Pemahaman dan Kepedulian dalam Penerapan Green Accounting pada UMKM Tempe di Kabupaten Sikka - Claudensia Yuli Lolan; Wilhelmina Mitan; Yoseph Darius Purnama Rangga (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine understanding and concern in implementing green accounting in Tempe MSMEs in Sikka Regency. This research uses a qualitative descriptive method. The data collection techniques used were interviews and documentation. The data analysis technique, namely descriptive analysis, begins with the data reduction stage, data presentation and conclusion drawing or verification. The research results show that tempe MSMEs in Sikka Regency, consisting of the Super Jaya tempe factory, Sidu Moro tempe factory, Bintang Jaya tempe factory, Putra Fajar tempe factory, have an understanding and concern for the environmental impact of the business activities they carry out. A manifestation of the understanding of tempeh MSMEs in Sikka Regency regarding the environment is by charging environmental costs in the tempeh production process. The environmental costs charged include the costs of storage tanks, filters, labs, plastic, banana leaves and waste. However, tempe MSMEs do not yet have sufficient understanding to apply the green accounting concept as a whole to the presentation of financial reports. The manifestation of concern for tempeh MSMEs in Sikka Regency is through maintaining business continuity, business raw materials, business waste, organic and non-organic waste, environmentally friendly equipment, understanding environmental costs and being directly assisted by the Health Service and the Sikka Regency Environmental Service.